Immigration reform under the Obama administration and its impacts on undocumented immigrants in the U.S. = Cải cách chính sách nhập cư dưới thời tổng thổng Obama và những tác động của cải cách đó tới người nhập cư bất hợp pháp ở Mỹ - Nguyễn, Thị Nguyệt Minh (2021)
A year before Barack Obama officially became the U.S. president, the number of illegal immigrants in the United States reached a peak of 12 million in 2008. Like previous presidents, he also has carried out reform in immigration policy to handle the increasing number of undocumented immigrants as well as problems posed by unauthorized aliens already entering the U.S. This dissertation is an attempt to find out major and significant changes in immigration platform under Barack Obama’s presidential terms as well as to analyze and illustrate impacts of this reform on undocumented immigrants residing in the U.S., especially the young who meet all criteria of the new policy. The research employs content analysis and secondary data analysis. For the first question of the study, three most noticeable immigration changes are revealed concluding strict enforcement at US border and the interior, effective worksite enforcement strategy and the implementation of the Deferred Action for Childhood Arrivals program (DACA). In term of impacts of immigration reform enacted by President Obama on undocumented immigrants, the researcher figures out three significant ones. The first is that DACA increases unauthorized aliens’ opportunities for integrating into social institution. Secondly, thanks for DACA implementation, undocumented immigrants get increasing access to the higher education which results in higher wages translating into the country’s economic growth via more tax revenue generated and more economic activities. Finally, DACA is an appropriate means helping undocumented immigrants and their families to get over psychological barriers such as fear, anxiety and stress of deportation